Novel High-Throughput Decoding Algorithms for Product and Staircase Codes Based on Error-and-Erasure Decoding - Sheikh, Alireza; Amat, Alexandre Graell i; Alvarado, Alex (Journal of lightwave technology, 2021)
Product codes (PCs) and staircase codes (SCCs) are conventionally decoded based on bounded distance decoding (BDD) of the component codes and iterating between row and column decoders. The performance of iterative BDD (iBDD) can be improved using soft-aided (hybrid) algorithms. Among these, iBDD with combined reliability (iBDD-CR) has been recently proposed for PCs, yielding sizeable performance gains at the expense of a minor increase in complexity compared to iBDD. In this paper, we first extend iBDD-CR to SCCs. We then propose two novel decoding algorithms for PCs and SCCs which improve upon iBDD-CR. The new algorithms use an extra decoding attempt based on error and erasure decoding of the component codes. The proposed algorithms require only the exchange of hard messages between component decoders, making them an attractive solution for ultra high-throughput fiber-optic systems. Simulation results show that our algorithms based on two decoding attempts achieve gains of up to 0.88 dB for both PCs and SCCs. This corresponds to a 33% optical reach enhancement over iBDD with bit-interleaved coded modulation using 256 quadrature amplitude modulation.